Politik Hukum Pembangunan Hukum Nasional dalam Garis-Garis Besar Haluan Negara Tahun 1973 dan Tahun 1978 - Fadli, Moh; Maulana, Iqbal; Liemanto, Airin (UNIVERSITAS ISLAM KADIRI, 2024)
This article aims to explore the legal policy on national legal development in the 1973 and 1978 Guidelines of State Policy of the Republic of Indonesia (GBHN). Through a normative legal research approach, incorporating statutory, historical, and conceptual analysis, the study reveals several key insights. First, the GBHN serve as the overarching framework for national development, ensuring continuity across various sectors to realize the national goals outlined in the Preamble to the 1945 Constitution. Pancasila and the 1945 Constitution are positioned as enduring legal policy. Second, both the 1973 and 1978 GBHN emphasize the creation, renewal, codification, and unification of laws. The legal policy on legal development outlined in the 1978 GBHN not only build upon but also expand the initiatives of the 1973 GBHN. The development of the national legal system in both guidelines occurs simultaneously, addressing the legal substance, structure, and culture within society. Third, while legal development is crucial, it is not the highest priority, as it is seen as a supportive element to the economic sector, which was considered more pressing at the time.